OECD in figures : statistics on the member countries - Organisation for Economic Co-operation and Development (Organisation for Economic Co-operation and Development, 2000)
OECD in Figures is OECD's pocket data book.It contains key data on OECD countries, ranging from economic growth and employment to trade and migration. There are comparable tables on the environment, science and public finances.For added perspective, OECD in Figures includes a selection of graphs, giving snapshots on subjects such as GDP, education spending, services trade, health funding, development aid and renewable energy.OECD in Figures 2005 isa StatLink publication. It includes links to downloadable Excel data underlying each chart and graph.